Yam glycoprotein mediated the immunomodulation of macrophages by targeting TLR4 - Yuzhi Luo; Siqi Wang; Lingyi Liu; Ruisi Zhu; Xiaoyue Wang; Yajing Ma; Huixin Song; Sha Wen; Lingli Li; Songyuan Xia; Weifeng Li; Xiaofeng Niu (Molecular Biology Reports, 2026)

pH regulation of 1,2-bis(trimethoxysilyl)ethane hydrolysis pathways for enhanced wet state stability of TEMPO-oxidized cellulose nanofiber aerogels - Aojia Zhang; Rui Teng; Quan Zhang; Xue Liu; Biyao Sun; Chengcheng Suo; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Mussel-inspired molecular strategy for ultrasensitive detection of multiple chiral molecules - Yanhong Liu; Yang Li; Chengcheng Suo; Wei Li; Sha Luo; Chunhui Ma; Shouxin Liu (Analytica Chimica Acta, 2026)

Inflammatory response involved in cartilage degeneration induced by T-2 toxin: systematic review - Qian Li; Yikai Hu; Juan Zuo; Zaichao Dong; Tongtong Sha; Kangting Luo; Miao Wang; Huanxia Zhang; Yanjie Dou; Shuiyuan Yu; Fang-fang Yu (Mycotoxin Research, 2026)

Combining Organic and Inorganic Amendments Simultaneously Mitigates Soil NH3 and N2O Emissions - Anrong Luo; Xiayan Zhang; Yunzhe Li; Shikang Li; Zhipeng Sha (International Journal of Environmental Research, 2026)

Tacrolimus combined with everolimus versus sirolimus in organ transplantation: a comparative pharmacovigilance analysis of the FDA Adverse Event Reporting System - Yanlang He; Chen Luo; Shuangyan He; Sha Li; Haolin Zhou; Sheng Wei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Intelligent identification and orientation information extraction of rock slope discontinuities from point cloud data based on LEKM-PointNet++ - Danni Zhao; Kun Li; Zixuan Zhang; Jiangbo Xu; Shengwen Qi; Peng Sha; Shaowei Wang; Guangming Luo; Bowen Zheng; Xiaolin Weng; Yalin Nan; Nengyuan Chen (Transportation Geotechnics, 2026)

Mining and characterization of endogenous constitutive promoters in Aspergillus oryzae - Sha Huang; Laimao Luo; Jingyin Zhou; Zhui Tu; Qinhua He; Yanping Li (Food Bioscience, 2026)

Scalable low-temperature synthesis of high-purity boron nitride nanotubes for high thermal conductivity composites - Xiaolu Sha; Jinang Li; Xiyue Li; Danni Zhao; Ze Long; Xinyu Zhao; Zhihua Luo; Jinling Gao; Wei Gao; Hong Yin (Chemical Engineering Journal, 2026)

Genome-wide insights into the regulatory networks of ZmHsf28 in salt and drought stress - Lijun Liu; Xia Zheng; Xiaoyu Sha; Shuaibing Tian; Ziyi Luo; Yuhan Zhang; Guocheng Wei; Yuxin Li; Jingye Fu; Qiang Wang (Plant Science, 2026)

Microwave pretreatment assisted regulation of surface oxygen density and narrow micropores of bamboo-based porous carbon for effective CO2 capture and H2 adsorption - Wanying Wang; Lishu Shao; Yongzhen Li; Xiancheng Ma; Weigang Zhao; Lei Li; Sha Luo; Yu Liao; Yan Qing (Journal of Environmental Chemical Engineering, 2026)

miR-133a-3p promotes T-2 toxin-induced chondrocyte damage via targeting IGF1R - Kangting Luo; Lingyu Wang; Zhengyan Zhang; Yikai Hu; Chengyu Zhao; Shuiyuan Yu; Qian Li; Zaichao Dong; Tongtong Sha; Miao Wang; Juan Zuo; Yanjie Dou; et al. (Chemico-Biological Interactions, 2026)

A Multi-omics Atlas of Gonadal Sex Differences and Characterization of the dmrt1 Gene in Gymnocypris Eckloni Herzenstein - Luo Lei; Yinhua Zhou; Qing Liu; Hejiao Li; Wuga Sha; Chaoyang Li; Suxing Fu; Yuting Duan; Rongrong Liao; Can Liu; Dapeng Gu; Linzhen Li; et al. (Marine Biotechnology, 2026)

Clinical application of MALDI-TOF MS for direct and rapid pathogen identification: a comprehensive review focusing on bloodstream infections and sterile body fluids - Chen Peng; Jie Hou; Xin Li; Ao Deng; Ze-Hao Wang; Xue-An Wang; Bin Yang; Li-Sha Luo (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Dual-Gradient Drilling and Riserless Mud Recovery Technology: A Review of Principles, Progress, and Challenges - Rongrong Qi; Hongfeng Lu; Zhibin Sha; Fangfei Huang; Yan Li; Zhiyuan Luo; Jinsong Lu (Journal of Marine Science and Engineering, 2026)
Deepwater drilling operations face critical challenges including narrow pore-fracture pressure windows, wellbore instability, and environmental concerns from drilling discharge. This paper presents a comprehensive systematic review of Riserless Mud Recovery (RMR) technology, tracing its evolution from its conceptual origins to its current applications, critically analyzing its technical limitations, and identifying future research directions. A systematic literature review was conducted covering peer-reviewed journals, SPE/IADC conference proceedings, industry technical reports, and independent academic studies from 1990 to 2025. Databases searched included Web of Science, Scopus, OnePetro, and Google Scholar, supplemented by Derwent Innovation Index for patents. After screening over 100 publications, approximately 60 references were selected following a two-step process excluding vendor-only promotional materials. Key findings reveal the following: (1) RMR technology has evolved through three distinct hardware generations—flexible hose systems, steel-pipe return lines with tandem pumps enabling deepwater breakthrough to 1419 m, and hybrid riser configurations for conceptual designs beyond 3000 m; (2) documented field benefits include 70% drilling fluid reduction, 9 days’ time savings per well, and successful mitigation of shallow geohazards across more than 1000 global well applications; (3) integration with casing-while-drilling and managed pressure cementing has enabled record-breaking performance of 1710 m in a single run; (4) independent academic validation confirms fatigue mechanisms affecting mud return lines; (5) systematic failure mode analysis identifies critical reliability issues in suction hoses, seals, and control systems; (6) quantitative economic analysis shows RMR cost-effectiveness depends on water depth, geological conditions, and environmental regulations. RMR technology has matured into a reliable drilling solution, yet its continued evolution requires addressing hardware limitations, developing dedicated well-control protocols, expanding to ultra-deepwater and emerging applications, and integrating digitalization for real-time optimization.

Unveiling Cl-induced electrocatalytic Cα-Cβ cleavage mechanism by 1D/2D/1D TiO2@ZIS-Sv@C heterojunction for efficient aromatic aldehyde generation - Jifang Zhang; Chengcheng Suo; Hongru Zhang; Wei Li; Sha Luo; Bing Tian; Chunhui Ma; Shouxin Liu (Journal of Environmental Chemical Engineering, 2026)

Systematic druggable genome-wide Mendelian randomization identifies therapeutic targets for gout - Wei-quan Liao; Hui-ying Chen; Yu-ying Li; Li-juan Xiao; Zai-xing Qiu; Sha-sha Hu; Si-hui He; Lan Luo; Jing-jing Xie; Jian-yong Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Novel phosphorus fertilizers enhance rice yield, efficiency, and environmental sustainability by optimizing soil phosphorus pools in paddy fields - Laichao Luo; Nannan Li; Wenzhuo Sha; Zhi Li; Rushan Chai; Liangliang Zhang; Chaochun Zhang; Kadambot H.M. Siddique (Soil and Tillage Research, 2026)

Dynamic hydrolytic ion-pairing enables stable interfaces and high anode utilization in lean-electrolyte Mg-air batteries - Yuxi Zhang; Sensen Yu; Ming Li; Sha Luo; Yu Feng; An Duan; Bao Zhang; Wei Sun (Chemical Engineering Journal, 2026)

Cellulose based hierarchical structural colored wood composite material for daytime radiative cooling - Biyao Sun; Shaoyi Cao; Shuliang Dou; Yudong Li; Wenye Sun; Chunhui Ma; Sha Luo; Mingcong Xu; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2026)

HIF-1α/BNIP3L–mediated mitophagy is involved in T-2 toxin–induced myocardial injury - Qian Li; Miao Wang; Juan Zuo; Zaichao Dong; Tongtong Sha; Kangting Luo; Huanxia Zhang; Yanjie Dou; Guoyu Zhou; Yue Ba; Fang-fang Yu (Chemico-Biological Interactions, 2026)

Straw return impacts on crop yield and yield variability: A meta-analysis - Kexin He; Bao-Luo Ma; Xiaofei Wei; Sha Guo; Chengcheng Feng; Chenyang Liu; Yongqing Ma; Pufang Li (Soil and Tillage Research, 2025)

Efficient HCHO oxidation via reaction and diffusion intensification on TOCNFs@MnOx - Ke Cheng; Xue Liu; Sha Luo; Ruiwen Wang; Chunhui Ma; Bing Tian; Wei Li; Shouxin Liu (Journal of Environmental Chemical Engineering, 2025)

Microbiome and pathogen identification, and associated antimicrobial resistance genes and virulence factors in seafood revealed by 16S rRNA amplicon and metagenomic sequencing - Xin Gao; Peiyong Ning; Sha Luo; Yuan Wang; Wen Li; Xiaoqing Fan; Xiaoyan Li (International Journal of Food Microbiology, 2025)

Deep eutectic solvent driven hydrogen bond confinement synthesis of multifunctional carbon dots from Licorice residues - Wenbo Cui; Xin Zhao; Jiali Song; Jianwei Zhao; Chunfa Zhang; Chunhui Ma; Mingcong Xu; Ruiwen Wang; Sha Luo; Shouxin Liu; Wei Li (Chemical Engineering Journal, 2025)

Prevalence and spectrum of STRC variants in 1015 sensorineural hearing loss patients: insights from the Chinese population - Luo Guo; Sha Yu; Wenrui Zhao; Liheng Chen; Guiqing Cheng; Weitao Li; Wei Li; Haiting Ji; Shan Sun; Huiqian Yu; Haiying Liu; Chunyi Gui; et al. (Molecular Genetics and Genomics, 2025)

Genetic analysis of patients with low-frequency non-syndromic hearing loss - Sha Yu; Weitao Li; Xinhao Lin; Liheng Chen; Wenxia Chen; Luo Guo; Yilai Shu (Molecular Genetics and Genomics, 2025)

Hydrofluoric-acid-mediated hydrothermal synthesis of anatase TiO2 with {101}/{001} facets for selective photocatalytic valorization of glycerol to syngas - Zheng Yang; Haoqiang Hou; Ermiao Liang; Kun Zhang; Mingcong Xu; Chunhui Ma; Wei Li; Sha Luo; Shouxin Liu (Journal of Environmental Chemical Engineering, 2025)

Photocatalytic biorefining green closed-loop: Photocatalytic alkali lignin depolymerization in supramolecular solvent - Chengcheng Suo; Xiaochang Zhang; Xinai Li; Jifang Zhang; Hongru Zhang; Rui Teng; Wei Li; Sha Luo; Bing Tian; Qingjiang Pan; Chunhui Ma; Zhijun Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Identifying gelatin source by mass spectrometry: A review - Xiao-Mei Sha; Le-Ying Yang; Hui Wang; Jie Cheng; Hao-Sheng Luo; Li-Jun Zhang; Zi-Zi Hu; Zong-Cai Tu (Food Chemistry, 2025)

Network pharmacology and molecular docking reveal the potential mechanisms of edible Fritillariae cirrhosae bulbus in alleviating asthma-related symptoms: A transcriptomics-supported study - Lingyi Liu; Ruisi Zhu; Yuzhi Luo; Lingli Li; Sha Wen; Songyuan Xia; Yajing Ma; Huixin Song; Weifeng Li; Xiaofeng Niu (Food Bioscience, 2025)

Metal-polyphenol network-hardened coconut protein-carboxymethyl cellulose complex coacervates: Fabrication, characterization, environmental stability, and release kinetics - Maye Li; Sha Luo; Chunmei Cheng; Xun Liang; Jing Xu; Zengwang Guo; Zhongjiang Wang; Lechuan Wang; Zhaoxian Huang; Lianzhou Jiang (Carbohydrate Polymers, 2025)

Mechanisms of groundwater recovery and land subsidence mitigation in a piedmont plain - Long Zhao; Xiao-Wei Jiang; Yu-Mei Li; Yong Luo; Kun-Chao Lei; Wen-Jie Kou; Fang Tian; Miao-Zhuang Tian; Te Sha; Shu-Fang Wang; Wen-Jun Cui (Journal of Hydrology, 2025)

Microbiome catalog and dynamics of the Chinese liquor fermentation process - Xue Zhu; Liangqiang Chen; Pengshuo Yang; Sha Luo; Mengjing Teng; Wenjie Zhu; Yuxue Li; Dan Zhao; Nan Wang; Xiaoke Chen; Mingyue Cheng; Huabin Tu; et al. (Bioresource Technology, 2025)

Straw return significantly enhances wheat yield in higher precipitation environment by promoting larger root diameters, wider xylem channels, and thinner root cortex - Xiaofei Wei; Kexin He; Bao-Luo Ma; Sha Guo; Chengcheng Feng; Chenyang Liu; Yongqing Ma; Pufang Li (Plant and Soil, 2025)

Hepatotoxic effects of exposure to different concentrations of Dibutyl phthalate (DBP) in Schizothorax prenanti: Insights from a multi-omics analysis - Luo Lei; Wuga Sha; Qing Liu; Shidong Liu; Yinhua Zhou; Rundong Li; Yuting Duan; Suxing Fu; Hejiao Li; Rongrong Liao; Linzhen Li; Rongzhu Zhou; et al. (Aquatic Toxicology, 2025)

Correction: Discovery of novel 4-trifluoromethyl-2-anilinoquinoline derivatives as potential anti-cancer agents targeting SGK1 - Guangcan Xu; Lanlan Li; Mengfan Lv; Cheng Li; Jia Yu; Xiaoping Zeng; Xueling Meng; Gang Yu; Kun Liu; Sha Cheng; Heng Luo; Bixue Xu (Molecular Diversity, 2025)

Discovery of novel 4-trifluoromethyl-2-anilinoquinoline derivatives as potential anti-cancer agents targeting SGK1 - Guangcan Xu; Lanlan Li; Mengfan Lv; Cheng Li; Jia Yu; Xiaoping Zeng; Xueling Meng; Gang Yu; Kun Liu; Sha Cheng; Heng Luo; Bixue Xu (Molecular Diversity, 2025)

Multiple stimuli-responsive circularly polarized luminescent bio-composite films by coassembling cellulose nanocrystals and curcumin - Shaoyi Cao; Jingpeng Wang; Wenye Sun; Bang An; Mingcong Xu; Sha Luo; Chunhui Ma; Haipeng Yu; Zhijun Chen; Jian Li; Wei Li; Shouxin Liu (Carbohydrate Polymers, 2025)

SYMRK significantly affected AMF symbiosis and plant growth in maize - Jing Zhou; Sha Lin; Xinhao Luo; Lixue Sun; Jin Chen; Beijiu Cheng; Xiaoyu Li (Plant Science, 2025)

Urbanization leads to convergent succession and homogenization of phytoplankton functional traits in a subtropical watershed over 11 years - Yifan Lu; Lei Jin; Huihuang Chen; Anqi Luo; Elias Ehrlich; Shuzhen Li; David M. Wilkinson; Zhansen Sha; Jun Yang (Environmental Research, 2025)

A novel framework for river organic carbon retrieval through satellite data and machine learning - Shang Tian; Anmeng Sha; Yingzhong Luo; Yutian Ke; Robert Spencer; Xie Hu; Munan Ning; Yi Zhao; Rui Deng; Yang Gao; Yong Liu; Dongfeng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Multi-organ toxicity caused by PM2.5 in mice with cardiovascular diseases: The role of PAHs played from the most polluted episodes in China - Jinjin Yu; Jian Sun; Yajing Ma; Xinyi Niu; Ruisi Zhu; Huixin Song; Lingyi Liu; Yuzhi Luo; Songyuan Xia; Jingyu Wang; Lingli Li; Sha Wen; et al. (Journal of Environmental Management, 2025)

Analysis of growth physiological changes and metabolome of highland barley seedlings under cadmium (II) stress - Yingyong Luo; Xian Huang; Ajia Sha; Jing He; Xiaodie Chen; Wenqi Xiao; Lianxin Peng; Liang Zou; Bingliang Liu; Qiang Li (Environmental Pollution, 2025)

Design and synthesis of N-aryl-2-trifluoromethyl-quinazoline-4-amine derivatives as potential Werner-dependent antiproliferative agents - Huimin Li; Jia Yu; Gang Yu; Sha Cheng; Hui Wu; Jiaomei Wei; Chang You; Kun Liu; Menghan Wang; Xueling Meng; Guangcan Xu; Heng Luo; et al. (Molecular Diversity, 2025)

1T/2H-MoS2/CdS heterojunction for the co-production of lactic acid photoreforming to hydrogen and value-added chemicals - Ermiao Liang; Xue Liu; Zheng Yang; Jifang Zhang; Yabo Qi; Rui Teng; Wenbo Cui; Mingcong Xu; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Journal of Environmental Chemical Engineering, 2024)

Butterfly wing-inspired superhydrophobic photonic cellulose nanocrystal films for vapor sensors and asymmetric actuators - Bang An; Mingcong Xu; Wenye Sun; Chunhui Ma; Sha Luo; Jian Li; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2024)

A Protocol for Body MRI/CT and Extraction of Imaging-Derived Phenotypes (IDPs) from the China Phenobank Project - Chengyan Wang; Shuo Wang; Sha Hua; Ruokun Li; Yan Li; Zhang Shi; Kai Feng; Lizhen Lan; Meng Liu; Xutong Kuang; Xueqin Xia; Shihai Zhao; et al. (Phenomics, 2024)

Balancing Maillard reaction products formation and antioxidant activities for improved sensory quality and health benefit properties of pan baked buns - Yao Tang; Yuan Huang; Mengru Li; Wen Zhu; Wei Zhang; Sha Luo; Yingying Zhang; Jie Ma; Yuqian Jiang (Food Research International, 2024)

Green chemistry closed-loop: Photocatalytic cleavage lignin β-O-4 bond utilizing visible light by Bi2O3/Bi2WO6 in deep eutectic solvent at room temperature - Chengcheng Suo; Jintao Yu; Jifang Zhang; Wei Li; Sha Luo; Chunhui Ma; Shouxin Liu (Biomass and Bioenergy, 2024)

The superior adsorption capacity of biogenic α-Mn2O3 in comparison to chemogenic α-Mn2O3 for five divalent heavy metal cations and the adsorption mechanism of biogenic α-Mn2O3: Experimental and DFT investigations - Mingzhen Hu; Huatao Sun; Jun Luo; Sha Chen; Ding Li (Journal of Environmental Chemical Engineering, 2024)

Glycoprotein from selenium-enriched yam activates immune cells and enhances intestinal immunity via the NF-κB signaling pathway - Siqi Wang; Jinjin Yu; Lili Zhou; Yuzhi Luo; Lingyi Liu; Sha Wen; Lingli Li; Yajing Ma; Huixin Song; Song Ming; Weifeng Li; Xiaofeng Niu (Food Bioscience, 2024)

Levels, sources, and health risk assessment of phthalate acid esters in indoor dust of various microenvironments in university - Jun Pan; Xin Li; Ping Ding; Haojie Luo; Sha Cai; Qing Ge; Liuyi Zhang; Guocheng Hu (Chemosphere, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Synergistic optimization of the water state and transport pathway in hydrogels via pullulan and directional Freezing-Assisted salting out for efficient evaporation - Huanwei Shen; Xiayue Yang; Wenhao Li; Zhihua Sha; Hongmei Luo; Zixuan Li; Sihan Dong; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Alleviation of cadmium uptake in rice (Oryza sativa L.) by iron plaque on the root surface generated by Providencia manganoxydans via Fe(II) oxidation - Ding Li; Zeping He; Sha Chen; Jinyuan Chen; Zhexu Ding; Jun Luo; Zongpei Li; Yuanyi Hu (Archives of Microbiology, 2024)

NSP4 promotes replication of porcine reproductive and respiratory syndrome virus-2 - Hang Zhang; Gan Li; Yajie Zheng; Qin Luo; Huiyang Sha; Wenchao Sun; Mengmeng Zhao (Veterinary Microbiology, 2024)

Knockdown of NUF2-derived exosomes can inhibit the migration and autophagy of BC cells and improve resistance to doxorubicin - Lin Luo; Tong Sha; Hongtao Li (Tissue and Cell, 2024)

Deeper root distribution and optimized root anatomy help improve dryland wheat yield and water use efficiency under low water conditions - Pu-Fang Li; Bao-Luo Ma; Xiao-Fei Wei; Sha Guo; Yong-Qing Ma (Plant and Soil, 2024)

Combining rigid and deformable groups to construct a robust birefringent crystal for compact polarization components - Zhipeng Du; Xianyu Song; Wei Liu; Ziyi Wang; Hongyuan Sha; Qianting Xu; Yang Zhou; Yanqiang Li; Junhua Luo; Sangen Zhao (Science Bulletin, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Visible-light-initiated air-oxygenation of 5-hydroxymethylfurfural to maleic acid by iron(III) chloride - Yabo Qi; Sha Luo; Wei Li; Shujun Li; Zhijun Chen; Bing Tian; Shouxin Liu (Chemical Engineering Journal, 2024)

Designed synthesis N-doped sulfonated bifunctional catalyst for efficient 5-hydroxymethylfurfural production: A pyridinic N-triggered proton-shift mechanism at basic sites - Yu Yin; Yabo Qi; Chunhui Ma; Zhenwei Wu; Wei Li; Sha Luo; Shouxin Liu (Fuel, 2024)

Promotion of rice seedlings growth and enhancement of cadmium immobilization under cadmium stress with two types of organic fertilizer - Liang Chen; Jingjing Ma; Sha Xiang; Lihong Jiang; Ying Wang; Zhihuan Li; Xianjing Liu; Shuyang Duan; Yuan Luo; Yunhua Xiao (Environmental Pollution, 2024)

Detection and analysis of landslide geomorphology based on UAV vertical photogrammetry - Rui Bi; Shu Gan; Xiping Yuan; Kun Li; Raobo Li; Weidong Luo; Cheng Chen; Sha Gao; Lin Hu; Zhifu Zhu (Journal of Mountain Science, 2024)

China's subtropical deciduous plants are more sensitive to climate change than evergreen plants by flowering phenology - Hong‐Li Li; Arshad Ali; Xu Luo; Ke Liao; Nan Sun; Ming‐Shan Xu; Long‐Bin Sha; Dong He; Yan‐Jun Du; Wei‐Wei Sun; Xiao‐Dong Yang (Global Change Biology, 2024)
The ongoing climate change‐induced shifts in flowering phenology have emerged as a consequential force impacting biodiversity and ecosystems. Despite the globally recognized significance of flowering phenology as a key reproductive attribute, studies in subtropical regions have been relatively fewer, particularly in comparison to temperate and cold regions. Additionally, the nuanced response of deciduous and evergreen plants to climate change remains insufficiently explored. In addressing this gap, we built a phenological model and a generalized linear mixed effect model to assess the differential responses of key flowering phenological traits, that is, first flowering date (FFD), peak flowering date (PFD), end of flowering date (EFD), and flowering duration (FD), to climate factors (temperature and precipitation) between deciduous and evergreen plants. We observed distinct responses in flowering phenological traits to climate change between deciduous and evergreen plants. Specifically, the advancement of FFD, PFD, and EFD in deciduous in response to temperature rise exceeded that in evergreen plants. FD in evergreen plants exhibited a stronger extension to temperature increase compared to deciduous. Conversely, the phenological change of evergreen plants in response to decreasing precipitation was greater than that of deciduous ones. Since temperature is a decisive climatic factor in affecting phenological changes, climate change‐induced advances in flowering phenology of deciduous plants are still larger than evergreen plants. Projections from our phenological model under future climate scenarios (SSP 1‐2.6 and SSP 5‐8.5) indicate a continuous enlargement of difference in flowering phenology between deciduous and evergreen plants, with this trend escalating into the future (2100>2070>2050>2030). The larger extension in FD of evergreens to climate change suggests a potential increase in their proportion within subtropical forest communities relative to deciduous plants. These insights contribute significantly to our understanding of the intricate dynamics of climate‐induced changes in subtropical plant ecosystems.

High Lewis acidity catalyst for direct depolymerization of microcrystalline cellulose to 5- hydroxymethylfurfural: Reaction optimization by central composite design - Yu Yin; Chunhui Ma; Wei Li; Sha Luo; Zhanshuo Zhang; Shouxin Liu (Biomass and Bioenergy, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Boerechalasins A–G, cytochalasans from the fungus Boeremia exigua with anti-inflammatory and cytotoxic activities - Si-Qiong Teng; Xiao-Fang Zhang; Hong-Fei Li; Xin-Wen Luo; Yang-Sha Zhou; Hui Liu; Ji-Kai Liu; Tao Feng (Phytochemistry, 2023)

Hierarchical wood cells impose well-textured carbon nanotubes with cobalt single atoms: Bioinspired construction and application in zinc–air battery - Yangyang Chen; Ying Wu; Lei Li; Yu Liao; Sha Luo; Han Xu; Yiqiang Wu; Yan Qing (Chemical Engineering Journal, 2023)

Phase change materials in food: Phase change temperature, environmental friendliness, and systematization - Chi Hu; Lishan Sha; Chongxing Huang; Wanru Luo; Bo Li; Haohe Huang; Chenglong Xu; Kaikai Zhang (Trends in Food Science & Technology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Liver transcriptome analysis and identification of differentially expressed immune gene response to Aeromonas veronii infection in Channa argus - Xiumei Chen; Jiasong Zhang; Muyang Li; Jiaxin Tian; Xiaotian Niu; Xiaofeng Shan; Sha Luo; Guiqin Wang; Aidong Qian (Aquaculture International, 2023)

Polysulfides manipulation: Constructing g-C3N4 networks encapsulated into natural wood fibers for high-performance lithium–sulfur batteries - Yangyang Chen; Ying Wu; Lei Li; Yu Liao; Sha Luo; Yiqiang Wu; Yan Qing (Chemical Engineering Journal, 2023)

[Cuproptosis-related immune gene signature predicts clinical benefits from anti-PD-1/PD-L1 therapy in non-small-cell lung cancer - Linfeng Luo; Anlin Li; Sha Fu; Wei Du; Li-Na He; Xuanye Zhang; Yixing Wang; Yixin Zhou; Yang Yunpeng; Zhang Li; Shaodong Hong (Immunologic Research, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Early Permian bimodal magmatism and tectonic evolution of the easternmost Paleo-Asian orogenic system - Xiaopeng Yang; Shichao Li; Weifeng Luo; Kunpeng Jiang; Zheren Zhao; Hongtao Wang; Hongyu Wei; Sha Dou; Jinfeng Jia; Zuoting Ren (International Journal of Earth Sciences, 2023)

Variations in the NSP4 gene of the type 2 porcine reproductive and respiratory syndrome virus isolated in China from 1996 to 2021 - Huiyang Sha; Hang Zhang; Qin Luo; Yajie Zheng; Qingge Zhu; Nina Wang; Limei Qin; Huawei Li; Liangzong Huang; Mengmeng Zhao (Virus Genes, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Correction: A novel lymphatic pattern promotes metastasis of cervical cancer in a hypoxic tumour-associated macrophage-dependent manner - Xiao-Jing Chen; Wen-Fei Wei; Zi-Ci Wang; Nisha Wang; Chu-Hong Guo; Chen-Fei Zhou; Luo-Jiao Liang; Sha Wu; Li Liang; Wei Wang (Angiogenesis, 2023)

Evolving a high-performance bio-imaging tool derived from a compact fluorophore as well as creating a reaction-based fluorescent probe for precise determination of Ag+ - Zi Yi Xu; Xiao Hu Wang; Sha Li Huang; Jing Rong Chen; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2023)

Landscape dynamics and human disturbance processes in wetlands in a mining city: a case study in Huaibei, China - Shiyuan Zhou; Jiang Chang; Pingjia Luo; Yuan Kang; Sha Li (Environmental Monitoring and Assessment, 2023)

Hypoxia Stress Induces Tissue Damage, Immune Defense, and Oxygen Transport Change in Gill of Silver Carp (Hypophthalmichthys molitrix): Evaluation on Hypoxia by Using Transcriptomics - Xiaohui Li; Chen Ling; Qiaoxin Wang; Cui Feng; Xiangzhong Luo; Hang Sha; Guoyu He; Guiwei Zou; Hongwei Liang (Frontiers in Marine Science, 2022)
The silver carp ( Hypophthalmichthys molitrix ) is an economically, as well as environmentally, important fish that harbors low environmental hypoxia tolerance and frequently contributes to a loss of aquaculture productivity. The gill is the first tissue attacked by hypoxia; however, the response of the gills of H. molitrix to hypoxia stress at the tissue, cellular, and molecular levels has not been clearly established. The influence of hypoxia on histological features along with gene expression in silver carp gills were explored in this research. The hematoxylin and eosin-stained sections and electron microscopy examinations of gills indicated that the gill lamellae were seriously twisted, gill filaments were dehisced, and the swelling and shedding of epithelial cell layer in the gill tissue were intensified along with the degree of hypoxia. In the hypoxia, semi-asphyxia, and asphyxia groups, the gill transcriptomic assessment of shifts in key genes, as well as modulatory networks in response to hypoxic conditions revealed 587, 725, and 748 differentially expressed genes, respectively. These genes are abundant in immune response signaling cascades (e.g., complement and coagulation cascades, Nucleotide-binding and oligomerization domain (NOD)-like receptor signaling cascade, and differentiation of Th1 along with Th2 cells) and oxygen transport [e.g., MAPK, PI3K-Akt, and hypoxia-inducible factor 1 (HIF-1) signaling cascades]. Genes linked to immune response (e.g., c2 , c3 , c6 , klf4 , cxcr4 , cd45 , and cd40 ) and oxygen transport (e.g., egln1 , egln3 , epo , ldh , and vegfa ) were additionally identified. According to our findings, the silver carp may be using “HIF-1” to obtain additional oxygen during hypoxia. These findings illustrate that hypoxia stress might damage gill tissue, trigger an immunological response, and activate HIF-1 signaling to increase oxygen availability under hypoxic situations. The findings of this work will help scientists better understand the molecular mechanisms driving hypoxia responses in hypoxia-sensitive fish and speed up the development of hypoxia-resistant varieties.

A soil-borne Mn(II)-oxidizing bacterium of Providencia sp. exploits a strategy of superoxide production coupled to hydrogen peroxide consumption to generate Mn oxides - Sha Chen; Zhexu Ding; Jinyuan Chen; Jun Luo; Xiaofang Ruan; Zongpei Li; Fengfeng Liao; Jing He; Ding Li (Archives of Microbiology, 2022)

A novel lymphatic pattern promotes metastasis of cervical cancer in a hypoxic tumour-associated macrophage-dependent manner - Xiao-Jing Chen; Wen-Fei Wei; Zi-Ci Wang; Nisha Wang; Chu-Hong Guo; Chen-Fei Zhou; Luo-Jiao Liang; Sha Wu; Li Liang; Wei Wang (Angiogenesis, 2021)
Lymphatic remodelling in the hypoxic tumour microenvironment (TME) is critically involved in the metastasis of cervical squamous cell carcinoma (CSCC); however, its underlying mechanisms remain unclear. Here, we uncovered a novel lymphatic pattern in the hypoxic TME, wherein lymphatic vessels (LVs) are encapsulated by tumour-associated macrophages (TAMs) to form an interconnected network. We describe these aggregates as LVEM (LVs encapsulated by TAMs) considering their advantageous metastatic capacity and active involvement in early lymph node metastasis (LNM). Mechanistic investigations revealed that interleukin-10 (IL-10) derived from hypoxic TAMs adjacent to LVs was a prerequisite for lymphangiogenesis and LVEM formation through its induction of Sp1 upregulation in lymphatic endothelial cells (LECs). Interestingly, Sp1 high LECs promoted the transactivation of C–C motif chemokine ligand 1 (CCL1) to facilitate TAM and tumour cell recruitment, thereby forming a positive feedback loop to strengthen the LVEM formation. Knockdown of Sp1 or blockage of CCL1 abrogated LVEM and consequently attenuated LNM. Notably, CSCC non-LNM is largely devoid of hypoxic TAMs and the resultant LVEM, which might explain its metastatic delay. These findings identify a novel and efficient metastasis-promoting lymphatic pattern in the hypoxic TME, which might provide new targets for anti-metastasis therapy and prognostic assessment.

Carbon material–immobilized ionic liquids were applied on absorption of Hg2+ from water phase - Lihan Sun; Mengru Wang; Wei Li; Sha Luo; Yan Wu; Chunhui Ma; Shouxin Liu (Environmental Science and Pollution Research, 2020)

Glutathione is Involved in Detoxification of Peroxide and Root Nodule Symbiosis of Mesorhizobium huakuii - Sha Luo; Jie Yin; Yang Peng; Jing Xie; Hetao Wu; Donglan He; Xiaohua Li; Guojun Cheng (Current Microbiology, 2020)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Global environmental costs of China's thirst for milk - Zhaohai Bai; Michael R. F. Lee; Lin Ma; Stewart Ledgard; Oene Oenema; Gerard L. Velthof; Wenqi Ma; Mengchu Guo; Zhanqing Zhao; Sha Wei; Shengli Li; Xia Liu; et al. (Global Change Biology, 2018)
China has an ever‐increasing thirst for milk, with a predicted 3.2‐fold increase in demand by 2050 compared to the production level in 2010. What are the environmental implications of meeting this demand, and what is the preferred pathway? We addressed these questions by using a nexus approach, to examine the interdependencies of increasing milk consumption in China by 2050 and its global impacts, under different scenarios of domestic milk production and importation. Meeting China's milk demand in a business as usual scenario will increase global dairy‐related (China and the leading milk exporting regions) greenhouse gas ( GHG ) emissions by 35% (from 565 to 764 Tg CO 2eq ) and land use for dairy feed production by 32% (from 84 to 111 million ha) compared to 2010, while reactive nitrogen losses from the dairy sector will increase by 48% (from 3.6 to 5.4 Tg nitrogen). Producing all additional milk in China with current technology will greatly increase animal feed import; from 1.9 to 8.5 Tg for concentrates and from 1.0 to 6.2 Tg for forage (alfalfa). In addition, it will increase domestic dairy related GHG emissions by 2.2 times compared to 2010 levels. Importing the extra milk will transfer the environmental burden from China to milk exporting countries; current dairy exporting countries may be unable to produce all additional milk due to physical limitations or environmental preferences/legislation. For example, the farmland area for cattle‐feed production in New Zealand would have to increase by more than 57% (1.3 million ha) and that in Europe by more than 39% (15 million ha), while GHG emissions and nitrogen losses would increase roughly proportionally with the increase of farmland in both regions. We propose that a more sustainable dairy future will rely on high milk demanding regions (such as China) improving their domestic milk and feed production efficiencies up to the level of leading milk producing countries. This will decrease the global dairy related GHG emissions and land use by 12% (90 Tg CO 2eq reduction) and 30% (34 million ha land reduction) compared to the business as usual scenario, respectively. However, this still represents an increase in total GHG emissions of 19% whereas land use will decrease by 8% when compared with 2010 levels, respectively.

MicroRNA-30e regulates neuroinflammation in MPTP model of Parkinson’s disease by targeting Nlrp3 - Dongsheng Li; Hongqi Yang; Jianjun Ma; Sha Luo; Siyuan Chen; Qi Gu (Human Cell, 2018)

The Role of Photoreceptors in Response to Cucumber Mosaic Virus in Arabidopsis thaliana - Xue Zhou; Tong Zhu; Li-Sha Zhu; Shi-Shuai Luo; Xing-Guang Deng; Hong-hui Lin; De-Hui Xi (Journal of Plant Growth Regulation, 2017)

Disturbance of chlorophyll biosynthesis at Mg branch affects the chloroplast ROS homeostasis and Ca2+ signaling in Pisum sativum - Sha Luo; Tao Luo; Peng Peng; Yanping Li; Xiaogang Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Generation and flanking sequence analysis of a rice T-DNA tagged population - Y. Sha; S. Li; Z. Pei; L. Luo; Y. Tian; C. He (Theoretical and Applied Genetics, 2004)